Approximation of the classes $B^{Ω}_{p, θ}$ of periodic functions of many variables by Fourier sums in the space $L_p$ with $p = 1, ∞$ - Myronyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain an exact-order estimate for the deviation of Fourier sums of periodic functions of many variables from the classes $B^{Ω}_{p, θ}$ in the space $L_p$ for $p = 1, ∞$.